N-(4-Methyl-2-pyridyl)-p-toluidine - Fairuz, Z.A.; Aiyub, Z.; Abdullah, Z.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C(13)H(14)N(2), the dihedral angle between the aromatic rings is 48.1 (1)degrees and the bridging C-N-C bond angle is 127.24 (12)degrees. In the crystal, intermolecular N-H center dot center dot center dot N hydrogen bonding about a center of inversion generates a hydrogen-bonded dimer.